Circumference determination and data extraction of two-dimensional circle / Siti Sarah Raseli ... [et al.] - Raseli, Siti Sarah; Abdul Ghafar, Nurul Munirah; Mahat, Norpah; Rosaidi, Nor Alifah (Universiti Teknologi MARA, Perak, 2019)
Shape is a space enclosed by an outline. For the purpose of this study, a circle shape is chosen. The objectives of this study are to determine the circumference and extract the data of circle’s circumference using the methods in Computer Aided Geometric Design (CAGD). This technique of circumference determination and data extraction can help the researchers for other processes involving the curve fitting and surface fitting in CAGD. In the first technique, the noise of the image was reduced by using Adobe Photoshop CS5. Next, the boundary image of circumference is extracted to determine the circumference of a circle. Then, the coordinate of the circumference was extracted using WebPlotDigitizer software. The solution from this study is a circumference of a circle and the data of a circle. This is a proposed alternative that can help researchers to proceed with another technique in CAGD such as corner points detection, control points determination, shape analysis and reconstruction of the curves and surfaces.